Chondroitin sulphate (WF6 epitope) levels in peri-miniscrew implant crevicular fluid during orthodontic loading - Intachai I. (2014)
The aim of this study was to monitor changes in chondroitin sulphate (CS; WF6 epitope) levels in peri-miniscrew implant crevicular fluid (PMICF) during orthodontic loading.Ten patients (seven males and three females; aged 22.0 ± 3.4 years), who required orthodontic treatment with extraction of all four premolar teeth, participated in the study. Twenty miniscrew implants (used as orthodontic anchorage) were placed, two in each patient, buccally and bilaterally in the alveolar bone between the roots of the maxillary posterior teeth. Sentalloy closed-coil springs (50 g) were used to load the miniscrew implants and to move the maxillary canines distally. During the unloaded period, PMICF samples were collected on days 1, 3, 5, and 7 after miniscrew implant placement and on days 14, 21, 28, and 35 during the loaded period. Clinical mobility assessments of the miniscrew implants were recorded at each visit. The competitive enzyme-linked immunosorbent assay with monoclonal antibody WF6 was used to detect CS (WF6 epitope) levels in the PMICF samples. The differences between the CS (WF6 epitope) levels during the unloaded and loaded periods were determined by a Mann-Whitney U-test.During the loaded period, two miniscrew implants were considered to have failed. The CS (WF6 epitope) levels during the unloaded period ranged from 0.00 to 758.03 ng/ml and those during the loaded period from 0.00 to 1025.11 ng/ml. Medians of CS (WF6 epitope) levels, around 'immobile' miniscrew implants, between the unloaded and loaded periods were not significantly different (P=0.07).CS (WF6 epitope) levels in PMICF can be detected and may be used as biomarkers for assessing alveolar bone remodelling around miniscrew implants during orthodontic loading. © The Author 2008. Published by Oxford University Press on behalf of the European Orthodontic Society. All rights reserved.